The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/polb.24602
|View full text |Cite
|
Sign up to set email alerts
|

A computational structure–property relationship study of glass transition temperatures for a diverse set of polymers

Abstract: The glass transition temperature (Tg) is one of the most important properties affecting the stability of a polymeric material. A cheminformatics‐based approach has been employed to investigate the glass transition temperatures for a set of polymers. Specifically, a set of 80 polymers was used to build a quantitative structure–property relationship (QSAR). By applying a combination of cheminformatics methods, several predictive models were developed consisting of 1–10 physicochemical variables. The best predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 29 publications
(78 reference statements)
0
18
0
Order By: Relevance
“…It is estimated that the flow velocity (i.e., the gradient of the displacement profile) in the flow stage was about 0.3 Å/ps, which was more than 30 times faster than that in the diffusion stage (~9.1 × 10 −3 Å/ps). Since pressure is the driving force for flow transportation, we can thus define a transition nominal pressure ( ) for the diamond nanochannel that determines when flow transportation occurred, similar to the definition of glass transition temperature in polymers [ 60 , 61 , 62 , 63 ]. As plotted in Figure 4 d, the pressure threshold between the diffusion and flow stages is defined as the transition nominal pressure, which was about 7.7 GPa for the diamond nanochannel.…”
Section: Resultsmentioning
confidence: 99%
“…It is estimated that the flow velocity (i.e., the gradient of the displacement profile) in the flow stage was about 0.3 Å/ps, which was more than 30 times faster than that in the diffusion stage (~9.1 × 10 −3 Å/ps). Since pressure is the driving force for flow transportation, we can thus define a transition nominal pressure ( ) for the diamond nanochannel that determines when flow transportation occurred, similar to the definition of glass transition temperature in polymers [ 60 , 61 , 62 , 63 ]. As plotted in Figure 4 d, the pressure threshold between the diffusion and flow stages is defined as the transition nominal pressure, which was about 7.7 GPa for the diamond nanochannel.…”
Section: Resultsmentioning
confidence: 99%
“…By solving the multi-electron system of the atom numerically, it was possible to know the structural, electronic, optoelectronic, thermodynamic, and other properties of atoms and compounds at quantum mechanical level theory [7][8][9][10][11][12][13][14][15]. With a large amount of chemical descriptor data availability, chem-informatic space saw the rise in statistical relations being derived between desired material properties and chemical descriptors in what came to be known as Quantitative Structure-Property/Structure-Activity studies and is said to have accelerated new material or drug molecule discovery [16][17][18][19][20][21].…”
Section: Computational Chemistry and Chem-informaticsmentioning
confidence: 99%
“…The GA‐MLR technique found that a model consisting of seven variables provided the best fit for the training and test data sets without overfitting. The nature of these structural descriptors indicated that the glass transition temperature could be governed by the electronegative groups on polymers …”
Section: Machine Learning For Polymer Systemsmentioning
confidence: 99%